Literature Review: Association Between DMPA Injectable Contraceptive Use and Menstrual Cycle Disorders in Family Planning Acceptors - Dwi Hariyanti Sholeha, Indah; Titik Nur Hasanah; Wildy Panca; Evangelina I. Amansia Magno; Julieta Gama; Ana Paula Ribeiro; Luvi Dian Afriyani (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Injectable contraception is one of the most popular choices among family planning users in Indonesia. Depo Medroxyprogesterone Acetate (DMPA) injectable contraception is one of the most widely used hormonal contraceptive methods in Indonesia and globally. Despite its high effectiveness in preventing pregnancy, the use of DMPA is known to cause various side effects, particularly disruptions to the menstrual cycle. Menstrual disorders such as amenorrhea, spotting, and irregular bleeding are among the most frequently reported reasons for discontinuation among acceptors, making a comprehensive understanding of their prevalence and underlying mechanisms essential in midwifery practice. This study aimed to identify and analyze the profile of menstrual disorders among DMPA injectable contraceptive acceptors based on findings from previously published studies, as well as to examine the relationship between the duration of DMPA use and the occurrence of menstrual disorders. This study used a literature review design with this systematization mapping evidence from intervention studies 2021–2026 using the PRISMA guide, with searches in Sage, PubMed, Springer Nature, Wiley, etc., via Boolean operators and MeSH keywords: ["Medroxyprogesterone Acetate" OR "Depo-Medroxyprogesterone Acetate" AND "Contraceptive Agents" OR "Contraceptive Effects" AND "Menstrual Cycle"]. Articles were assessed using PICOS and methodological quality (study design, data extraction, risk of bias, synthesis). Of the 309 articles identified, 69 remained after full-text/open access filtering, and 12 after inclusion/exclusion criteria. Results of this study was the 12 articles analyzed, the majority found a significant association between the use of DMPA injectable contraception and menstrual disorders. Amenorrhea was the most dominant disorder, with a prevalence ranging from 50% to 75% across studies. Other disorders identified included spotting (33.3%–74%), hypomenorrhea, polymenorrhea, menorrhagia, and metrorrhagia. Long-term DMPA use (more than one year) was consistently associated with an increased risk of amenorrhea, mediated through suppression of the Hypothalamic–Pituitary–Ovarian (HPO) axis, resulting in decreased levels of FSH, LH, and estradiol, as well as endometrial atrophy. One study reported no significant association (p=0.852), which may be attributed to differences in sample characteristics and measurement methods applied. Conclusionon this study was the use of DMPA injectable contraception is strongly associated with menstrual disorders, particularly amenorrhea, the prevalence of which increases with longer duration of use. These disorders arise from hormonal suppression of the HPO axis, leading to inhibition of ovulation and endometrial atrophy.